Efficacy and safety of belimumab given for 12 months in primary Sjögren's syndrome: the BELISS open-label phase II study. (4th August 2015) - De Vita, Salvatore; Quartuccio, Luca; Seror, Raphaèle; Salvin, Sara; Ravaud, Philippe; Fabris, Martina; Nocturne, Gaétane; Gandolfo, Saviana; Isola, Miriam; Mariette, Xavier
Abstract: Objective. To report the efficacy and safety of long-term treatment of SS with belimumab, targeting the B-cell-activating factor. Methods. Patients with primary SS were included in the BELISS open-label phase II study, a 1-year open-label trial, if they were positive for anti-SSA or anti-SSB antibodies and had systemic complications or persistent salivary gland enlargement or early disease or biomarkers of B-cell activation. They received belimumab, 10 mg/kg i.v., at weeks 0, 2 and 4 and then every 4 weeks; if response was observed at week 28, or if the clinician and the patient agreed to continue the study in the absence of side effects, treatment was continued for 1 year. Efficacy and safety were analysed during the 1-year period of treatment. Results. Among the 30 patients recruited, 28 were evaluated at week 28 as already reported. Nineteen terminated the 52-week study, 15 of them being responders and 4 non-responders at week 28. Thirteen of the 15 responders at week 28 also responded at week 52 (86.7%). The improvement in the EULAR Sjögren's Syndrome Disease Activity Index and EULAR Sjögren's Syndrome Patient Reported Index scores observed at week 28 showed a trend to further improvement at week 52, and the amelioration of peculiar EULAR Sjögren's Syndrome Disease Activity Index domains (glandular, lymphadenopathy, articular) appeared of particular relevance. The decrease in biomarkers of B-cell activation observed at week 28 persisted unchanged until week 52, with RF decreasing further. Salivary flow, Schirmer's test and the focus score of salivary biopsy did not change. Safety of treatment was good. Conclusion. Long-term treatment with belimumab may be beneficial in SS. Randomized, double-blind, controlled studies in larger populations are encouraged.